FENOMENA RENDAHNYA NALAR DIGITAL MASYARAKAT INDONESIA: ANALISIS PERILAKU NETIZEN DAN SOLUSI PENDIDIKAN - Surya Putra, Wiene; Karina Wanda (Indonesian Journal of Islamic and Social Science, 2025)
This study investigates the underlying causes of low digital reasoning among Indonesian netizens, examining their online behaviors from an educational perspective, and proposing comprehensive, education-based solutions. Employing an explanatory sequential mixed methods design, the study first quantitatively assesses the prevalence and characteristics of low reasoning behaviors (eg, hoax sharing, hate speech, impoliteness) among a representative sample of Indonesian netizens. Subsequently, qualitative data will be collected through interviews and focus group discussions with educational stakeholders (teachers, students, policymakers) to explore the educational factors contributing to these behaviors and identify potential pedagogical interventions. Preliminary findings indicate a strong correlation between low digital literacy (particularly critical evaluation skills) and the propensity to spread misinformation and engage in uncivil online discourse. A significant gap exists in the formal education system regarding the explicit teaching of critical thinking, media literacy, and digital ethics. The study highlights the urgent need for integrated educational reforms that prioritize digital literacy, critical thinking, and character education across all levels of the Indonesian curriculum. These interventions are crucial for fostering a more discerning, responsible, and civically engaged digital citizenship.